Tissue changes in senescent gerbil prostate after hormone deprivation leads to acquisition of androgen insensitivity - Campos, Silvana G. P. [UNESP]; Goncalves, Bianca F. [UNESP]; Scarano, Wellerson R. [UNESP]; Corradi, Lara S. [UNESP]; Santos, Fernanda C. A. [UNESP]; Custodio, Ana M. G. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Goes, Rejane M. [UNESP]; Taboga, Sebastiao R. [UNESP] (Wiley-Blackwell, 2010)
P>The present study examined the response of the prostate epithelium of senescent gerbils submitted to orchiectomy and with or without steroidal blockade. Animals were divided into five groups, all surgically castrated except the control group composed of intact animals. In the experimental groups, doses of flutamide and/or tamoxifen were applied for 1, 3, 7 and 30 days postcastration. The structural methods applied reveal that castration, whether associated or not with anti-steroidal drugs, promoted short- and long-term decrease in wet and relative weights of the prostate. The quantitative decline of epithelial compartment proportion observed at the end of treatment was due to the sum of slight changes in the epithelium and lumen. The apoptotic index had risen significantly at 1 day and declined at 7 days postcastration. Androgen receptor (AR) expression decreased after 3 days of hormonal ablation, coinciding with the highest levels of apoptosis and cell proliferation observed in all treated groups. The majority of cells remained differentiated in all groups due to CK 8/18 expression. Some animals remained with injuries such as carcinomas and adenocarcinomas after hormonal ablation. In the latter a mixture of AR-positive and AR-negative cells was identified. Microinvasive carcinomas found in the group treated for 30 days consisted of PCNA-positive, inflammatory and non-proliferating cells. Low apoptosis incidence and bcl-2 positive cells were observed in these lesions. The treatments promoted a reduction of lesions in older gerbils, but treatment-resistant tumours will improve understanding of the events that lead to hormone resistance.
Keywords: apoptosis; castration; cell proliferation; flutamide; prostate cancer; senescent gerbil; tamoxifen